Pendidikan dalam Perspektif Islam: Tinjauan terhadap Pemikiran Muhammad Natsir - Abdul Rohman (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Education in Islamic Perspectives: A Review of Muhammad Natsir's Thought. Natsir's thought in education is inevitably related to his social, political, and religious background, although his religious comprehension is dominant. According to Natsir, education is an effort to build the human beings physically and spiritually to be a perfect one. The physical and spiritual perfection is indicated by the worldly-material need fulfillment and the hereafter-spiritual need fulfillment combined. The only way to the ultimate goal is tauhid as a foundation. The objective of education is to create generations possessing independence, creativity, and spirit to do what others did not do. Education needs to avoid creating generations dependent on others.